Examination of salt quality of Sereflikochisar Lake used in the Turkish leather industry - (:unkn) unknown (SOC LEATHER TECHNOL CHEMISTS, 2002)
Sereflikochisar Salt Lake is one of the largest in Central Turkey. This lake is a major source of salt that is used in preservation of animal hides in the Turkish Leather Industry. Due to the economic importance of the salt obtained from Sereflikochisar Salt Lake, preliminary microbial research has been performed and the salt quality of this lake evaluated. The pH of the brine and salt samples was between 7.02 - 7.97. Chemical analyses showed that the brine and salt samples contain sufficient ions, organic substances and hardness to support the growth of extremely halophilic bacteria. Halophilic microorganisms found in Sereflikochisar Salt Lake were isolated and at least partially characterised. The brine taken from Sereflikochisar Salt Lake contained 10(5) colony-forming units/ml of extremely halophilic bacteria. The salt crystals collected from Sereflikochisar Salt contained 10(5) - 10(7) colony-forming units/g of extremely halophilic bacteria. Colony pigmentation of these samples ranged from a deep blood-red to pale-orange as well as transparent colonies. Eighteen gram negative extremely halophilic aerobic strains were isolated from Sereflikochisar Salt Lake. All strains grew in 2.5 - 4.3 M NaCl (15-25% wt/vol) and they grew very well in 25 % (w/v) NaCl containing complex growth media at 39 C and at pH 7.0, they did not grow at a pH of 9-11. When grown under optimum conditions, the cells were pleomorphic rod-shaped and motile. Red pigmentation was also seen in the liquid media containing 25 % (w/v) NaCl. Most colonies were 1 to 4 mm diameter. The colonies were circular, margins were entire and undulate. Elevation of the strains was convex, raised and pulvinate. Pellicule, ring formation, sediment and cloudy growth of these strains were seen in the liquid media. Most of these strains were found to be susceptible to bacitracin (IOU) and rifampicin 5 mug but resistant to erythromycin (15mug), chloramphenicol (30mug), penicillin G (IOU), gentamicin (10mug), cefadroxil (30mug), sulfamethoxazole (23.75mug) and trimethoprime (1.25mug), tetracycline (30 mug), ciprofloxacin (5mug), amikacin (30mg), novobiocin (5mg), ampicillin (140mg) and neomycin (30mg). All of the strains showed negative starch hydrolysis, Voges-Proskaeur reactions and DNase activities. All of the strains showed positive methyl red reactions. Most of the strains showed negative indol production and positive gelatin, casein and Tween 80 hydrolysis, arginine dihydrolase, lysine decarboxylase, oxidase and catalase activities. Seven of 18 strains reduced nitrate to nitrite and formed gas from nitrate. D-Glucose, maltose, lactose, sucrose and D-mannitol were used as single carbon sources by some of the strains. Most of the strains have been found to produce acid from glucose. Ten, 7, 4 and 5 of the 18 strains produced acid from maltose, lactose, sucrose and mannitol, respectively. These studies show that Sereflikochisar Salt Lake contains a viable and diverse bacterial community, Seventeen of the eighteen strains showed positive gelatinase activity. The salt obtained from the lake should not be used directly to preserve hide due to the high number of proteolytic strains it contains.
Keywords: CURED CATTLE HIDES; HALOPHILIC BACTERIA; PRESERVATION; NOV